Spanish seamen, with attached statement (circular) - Tewson, Vincent
1939-12-05 025a-0073-002 EMPLOYMENT OF ALIENS. EMPLOYMENT OF ALIENS. Statement by the Home Secretary 23 November, 1939. As I have already indicated, His Majesty's Government desires to utilise the services of friendly aliens in any direction in which they can be advantageously employed without prejudice to the interests of British nationals. To this end I have made an Order under the Aliens Order under which aliens who arrived in this country before 3rd September last, and whose stay is subject to conditions, may take employment in Great Britain. They will only be able to do so, however, if permission if granted by My Right Honourable Friend, the Minister of Labour and National Service. The permission will be given by means of an endorsement on the alien's certificate of registration for a specific employment and it will be a requirement that any subsequent change of employment must be approved by the Minister in the same way. This scheme will apply to Germans and Austrians who have been exempted by a Tribunal from the restrictions applicable to enemy aliens in the same way as it applies to other aliens. My Right Honourable Friend, the Minister of Labour and National Service, informs me that in considering whether permission should be granted in any case full regard will be had to the views of Trade Unions or similar organisations. While it is not to be expected that at the present moment opportunities for employment will be available for any large number of aliens covered by the Order, the services of certain classes of alien workers possessing high technical skill may be found immediately useful. Instructions to the Local Offices of the Ministry of Labour and National Service contain specific directions that Local Officers should not submit an alien for a vacancy unless they are satisfied that no suitable British worker is available. As a measure of security the Order also requires that an alien shall not without special permit take employment in a prohibited place within the meaning of the Official Secrets Act, 1911, as subsequently amended, or a protected place within the meaning of Regulation 12 of the Defence Regulations, or in any of the auxiliary war services set out in a schedule to the Order. AC. 292/946/25a/73(ii)